The Cistercians and the Glossa Ordinaria: A Status Quaestionis - Dietz, Elias (Cistercian studies quarterly, 2015)
The article examines the relationship between 12th century Cistercian culture and the collection of Biblical glosses called, Glossa ordinaria (Gloss). An overview of Gloss is provided which was started in the 12th century, with the first books attributed to theologian Anselm of Laon. Other topics include medieval Cistercian literature, Gloss as a standardized reference work, and its influence on Cistercian writers.